Assessment of shared decision making in pediatrics: developing German scales for patients aged 7-18 years, parents and parent-proxy reports (CollaboRATEpediatric) - Herrle, Angélique; Görig, Tatiana; Georg, Sabine; Bock, Freia de; Ullrich, Charlotte; Eichinger, Michael (Patient education and counseling, 2021)
Objective - To develop parsimonious German scales (CollaboRATEpediatric) to assess shared decision making (SDM) with patients aged 7-18 years, parents and parents on behalf of their children (parent-proxy reports), and to establish comprehensibility and preliminary face validity. - Methods - Based on an existing SDM scale for adults (CollaboRATE) we developed CollaboRATEpediatric in a two-step approach: (1) team-based translation of the English CollaboRATE scale into German and adaptation for pediatric patients, parents and parent-proxy reports, followed by (2) iterative revisions of the CollaboRATEpediatric scales based on cognitive interviews with patients and parents until comprehensibility and preliminary face validity were established. - Results - Taking into account seven problem areas identified in four rounds of cognitive interviews (e.g., item complexity) we developed CollaboRATEpediatric scales for patients, parents and parent-proxy reports. By iteratively revising items we were able to resolve all problem areas and achieved full comprehensibility and intended interpretation of all items. - Conclusion - The scales enable the parsimonious assessment of SDM with pediatric patients and parents as well as comparisons between the two groups. Future empirical work will establish the psychometric performance of CollaboRATEpediatric. - Practice Implications - CollaboRATEpediatric can be used in quality improvement initiatives to foster the comprehensive implementation of SDM in pediatrics.
Im Titel ist pediatric bei CollaboRATE hochgestellt
Available online 5 September 2020
Gesehen am 29.06.2021